2005
DOI: 10.1111/j.1525-1497.2005.05007.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring faculty in academic medicine

Abstract: In this paper, we discuss an alternative structure and a broader vision for mentoring of medical faculty. While there is recognition of the need for mentoring for professional advancement in academic medicine, there is a dearth of research on the process and outcomes of mentoring medical faculty. Supported by the literature and our experience with both formal dyadic and group peer mentoring programs as part of our federally funded National Center of Leadership in Academic Medicine, we assert that a group peer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
212
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(220 citation statements)
references
References 36 publications
1
212
0
7
Order By: Relevance
“…5 A few studies measuring research productivity reported that those who had experienced mentorship reported greater productivity and rated their research skills more highly than those who did not identify a mentor. [6][7][8][9] Nonetheless, in reviewing available studies on mentorship between 1960 and 2006, Sambunjak et al 10 concluded that "mentoring is perceived as an important part of academic medicine, but the evidence to support this perception is not strong." Indeed, this review pointed out significant variation across studies regarding the definition of mentoring, functions of the mentor, and the time devoted to the mentor-mentee relationship.…”
Section: Introductionmentioning
confidence: 99%
“…5 A few studies measuring research productivity reported that those who had experienced mentorship reported greater productivity and rated their research skills more highly than those who did not identify a mentor. [6][7][8][9] Nonetheless, in reviewing available studies on mentorship between 1960 and 2006, Sambunjak et al 10 concluded that "mentoring is perceived as an important part of academic medicine, but the evidence to support this perception is not strong." Indeed, this review pointed out significant variation across studies regarding the definition of mentoring, functions of the mentor, and the time devoted to the mentor-mentee relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have outlined how to conduct research 1,2 and the importance of having a good mentor [3][4][5][6] . We hope that the present article, with its 10 pragmatic tips, will help junior researchers ultimately to publish their work.…”
mentioning
confidence: 99%
“…Literature has suggested that improved academic grades, knowledge and skills learned, attendance rates, enhanced self-esteem, improving communication skills, and decreasing incidents of questioning and warning letters are all possible measure tools that could be used in mentorship process [9]. The bottom-line is that success of the mentee is always an indicator of successful mentorship [10].…”
Section: Discussionmentioning
confidence: 99%